MINERAL CHEMISTRY AND THE PETROGENESIS OF EUCRITES: II. CUMULATE EUCRITES - Weibiao H.; Crozaz G. (My University, 1997)
We carried out an ion microprobe study of REEs and other selected trace and minor element concentrations in orthopyroxene, augite lamellae, and plagioclase of two cumulate eucrites Moama and Moore County in order to reevaluate the relationships between cumulate and noncumulate eucrites and among cumulate eucrites.Pyroxene and plagioclase in these two meteorites are more homogeneous in major, minor, and trace elements than in noncumulate eucrites, and trace and minor element concentrations in Moore County are higher than in Moama. Although subsolidus equilibration erased any original igneous zoning, it did not affect the REE patterns of these minerals. Both pigeonite and plagioclase of Moama and Moore County have higher LREE/HREE ratios than those phases in noncumulate eucrites. This indicates that cumulate eucrites derived from melts with fractionated REE patterns and, thus are not related to noncumulate eucrites. In addition, the inconsistency between degrees of fractional crystallization deduced from major and trace elements and the differences of LREE/HREE ratios recorded in pigeonite and plagioclase also suggest that Moama and Moore County did not form in the same fractional crystallization sequence. This study confirms earlier observations and conclusions of Ma and Schmitt (1979) and poses problems for prevalent models.